Simplified deployment of health informatics applications by providing docker images - Loebe, Matthias; Ganslandt, Thomas; Lotzmann, Lydia; Mate, Sebastian; Christoph, Jan; Baum, Benjamin; Sariyar, Murat; Wu, Jie; Staeubert, Sebastian (Studies in Health Technology and Informatics, 2017)
Due to the specific needs of biomedical researchers, in-house development of software is widespread. A common problem is to maintain and enhance software after the funded project has ended. Even if many tools are made open source, only a couple of projects manage to attract a user basis large enough to ensure sustainability. Reasons for this include complex installation and configuration of biomedical software as well as an ambiguous terminology of the features provided; all of which make evaluation of software laborious. Docker is a para-virtualization technology based on Linux containers that eases deployment of applications and facilitates evaluation. We investigated a suite of software developments funded by a large umbrella organization for networked medical research within the last 10 years and created Docker containers for a number of applications to support utilization and dissemination.
CRIS-Team Scopus Importer:2021-11-16
Keywords: Cloud; Container; Deployment; DevOps; Docker; IT infrastructure; Microservices; PaaS